Investigation of Technological Operations Affecting the Determination of Concentration of Ionol Additive in Insulating Oil in High-Voltage Equipment - Korobeynikov S.M.; Lyutikova M.N. (Problems of the Regional Energetics)
Ionol oxidation inhibitor level control is included into normative indicators list for diagnostics of internal insulation condition of any oil-filled high voltage device. Concentration of oxidation inhibitor in dielectric liquid should be from 0,08 % to 0,40 % mass. Power supply network chemistry laboratories use such methods as spectroscopy, spectrometry, chromatography and many others. Russian insulation service specialists use the method of ionol concentration measurement in oils based on gas-liquid chromatography. In the first place it is related to the fact that gas chromatographs are installed for several tasks, including definition of inhibitor’s mass concentration. However, as practice shows, the use of this method for additive analysis, especially in old acidified mineral oils is linked to some difficulties. The aim of this work is identify technologic faults that may occur during definition of ionol inhibitive additive in dielectric liquid with gas-liquid chromatography method, and, as a consequence, may lead to incorrect calculation of ionol additional concentration to oil, necessary for its antioxygenic properties maintenance and high insulation quality provision during high voltage device functioning. The object of the research is insulating oil with more than 35 years’ operating cycle, presenting a complex multiplex matrix of hydrocarbons and oxygenates preventing reliable determination of ionol additive with gas-liquid chromatography method. Executed researches show that the main input into “correct” final result obtention during calculation of additional additive concentration was made by such technological operations as water content in extractant and technology of sample introduction into chromatograph’s evaporation tank